Facts about Wildlife Diseases: Hemorrhagic Fever in White-Tailed Deer - Katherine A. Sayler; Charlotte Dow; Samantha M. Wisely (EDIS)
The viruses that cause hemorrhagic disease (HD) in deer do not cause illness in people, but they are a growing problem. HD is the most important viral disease of white-tailed deer in the United States. Large outbreaks have occurred in the northern Midwest and western United States. In Florida, outbreaks are fewer and less severe in populations of wild white-tailed deer than are outbreaks among wild deer in other areas of the United States, but farm-raised deer in the state are proving vulnerable to epizootic hemorrhagic disease virus: one of the viruses that cause HD.